The rejuvenation on historical ruined vaults using lab analyses and numerical simulation. (August 2019) - Cosgun, Turgay; Sayin, Baris; Gunes, Baris; Avşar, Ali Osman; Dönmezler, Maksut; Acıoğlu, Yusuf
Abstract: The exposure of historical masonry structures to climatic conditions and to user interventions, as well as the loss of their functionality over time, leads to the divergence of these structures from their original form and their dilapidation into ruin. With the aim of preserving such structures as cultural assets, the material characteristics of the original members are determined in a laboratory and their seismic capacity is determined by means of numerical analyses. The present study covers the works carried out to return to its original form a ruined vault in a historical castle that was built as a defensive structure in early 1800s, but which has in time lost its structural integrity. The study consisted of four stages: field work, laboratory analysis, preservation applications and a numerical simulation of the examined structure. The field study involves a visual inspection of structural deterioration and the gathering of representative samples from various points of the structure. The laboratory study includes mechanical, chemical and mineralogical analyses of the samples taken from the structure. Applications for the restoration of the structure to its original form are presented in the third stage, while the seismic performance level of the structure against seismic effects is defined. The study is important in its presentation of the process of reverting a vault structure that has suffered a deterioration of structural integrity over time into its original form from a geometric and material point of view. Such vaults are of particular importance as elements of castle structures that were used for defensive purposes at the time. The findings obtained from the research have been foreseen to contribute the understanding of structural behavior and intervention decisions in the restoration process of load-carrying brick vault systems in historical structures. Highlights: It is investigated that structural problems and physical deteriorations in the historical ruined vault. The laboratory tests and in situ analysis have been performed over samples gathered from the ruined structure. The preservation and repair applications are presented regarding the ruined structure. Numerical analyses are performed to determine the seismic resistance of the structure after the applications.